Syntactic diacrisis in a rigid and a free word order language - Zabrocki, Tadeusz (Investigationes Linguisticae, 2016)
The paper is concerned with some syntactic consequences of Polish being a synthetic language with a rich system of case inflections and English lacking morphological case (or having a residual form of it). It will be argued that this typologically significant grammatical difference provides an essential premise in a unified explanation for the clustering of a number of syntactic differences between the two languages. The argument is based on a set of functionally motivated constraints on grammatical representations. The constraints are proposed as a part of a theory of “syntactic diacrisis” and are claimed to result from a) the general nature of language as a semiotic system, and b) the specific properties of the human parsing mechanism. The paper consists of three sections. The first contains a brief discussion of the role and place of functional explanations in syntax and introduces the concept of a “parser’s requirement on structure” (PROS). The second section introduces and justifies some basic principles of “syntactic diacrisis”. The third focuses on several syntactic differences between English and Polish and shows how they could all be explained by reference to the interplay of the functional (theory of diacrisis)and grammatical factors.